MOTIVASI PENYULUH DALAM MELAKSANAKAN PENYULUHAN PERKEBUNAN KARET DI KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI - Andreas ' Manurung; Rosnita ' '; Cepriadi ' ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The objectives of research on motivation in carrying out the role of extension educator rubber plantations at kuantan Tengah sub district in Kuantan Singingi District are : a) studying counseling implementation rubber plantations, b) analysing motivational counseling in conducting counseling rubber plantation. The research uses surveyand interview. Intake of respondents were 6 instructors. The data analysis used is Skala Likert’s SummatedRating (SLR).The results showed counseling implementation rubber plantation has been running with good views of elements extension such as, a) Agriculture extension amonted to six people with a village built as much 3-4 villages, b) Target extension located in the estate UPTD Kuantan TengahSub District is rubber farmers, c) Extension methods used still refers to LAKU system (exercise and visit), d) Media outreach is used in the form of brosures, pemphlets and others, e) material submitted by extension workers to farmers in accordance with the programming and work plan extension. The research also showed that factors affecting motivation extension to decrease the rubber farmers in Kuantan Tengah Sub District are job satisfaction, compensation and warranty career affect significantly. Good supervison, fatigue and boredom are effect but not significant. While education level, personal marturity, regulation, disire work and work enviroment has no significant effect that can decrease work motivation extension. Keywords : Motivation, extension, rubber